A method for manufacturing a high abrasion resistant conveyor belt

By processing limiting grooves on PEKK film and combining them with TPU film, the problems of wear resistance and adhesion of lightweight conveyor belt materials have been solved, realizing a manufacturing method for conveyor belts with high wear resistance and high corrosion resistance.

CN117532929BActive Publication Date: 2026-11-06SHANGHAI YONGLI BELTING +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311445419.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2026-11-06
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

Existing lightweight conveyor belt materials such as PVC and TPU have insufficient wear resistance and corrosion resistance, making it difficult to meet the requirements of certain conveying scenarios. Furthermore, PEKK materials are difficult to bond effectively with conventional materials.

Method used

The system combines a PEKK film and a TPU film with a positioning groove structure. By processing the positioning groove on the surface of the PEKK film and infiltrating the groove with the TPU film, a stable connection is formed. The middle layer uses polyurethane material to enhance the bonding strength.

Benefits of technology

It improves the wear resistance and corrosion resistance of the conveyor belt, extends its service life, and meets the high wear resistance requirements for lightweight conveyor belts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117532929B_ABST
    Figure CN117532929B_ABST
Patent Text Reader

Abstract

This invention discloses a method for manufacturing a high-wear-resistant conveyor belt, comprising the following steps: fabric weaving and shaping; applying adhesive primer to the front and back sides of the fabric; casting a TPU film on the fabric surface; heat-processing a limiting groove on the surface of a PEKK film; and then heat-melting the TPU film on the fabric surface and allowing it to flow into the limiting groove on the PEKK film surface, thereby bonding the PEKK film to the TPU film. Compared with the prior art, the high-wear-resistant conveyor belt provided by this invention has a PEKK film surface, wherein a special microstructure is processed on the PEKK film surface, allowing the intermediate TPU layer to be embedded into the PEKK film surface, ensuring a stable bond between the two. That is, the PEKK film and polyurethane are physically bonded together, thereby fixing the PEKK to the entire surface layer of the conveyor belt. This provides a lightweight conveyor belt that meets the requirements for conveying corrosive materials and demanding wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical engineering, specifically relating to a highly wear-resistant and corrosion-resistant conveyor belt and its manufacturing method. Background Technology

[0002] With the improvement of industrial automation and the gradual miniaturization of equipment, traditional rubber belts are gradually being replaced by lightweight conveyor belts because their processing has a significant impact on the environment, the belt body is relatively thick, and the weight is relatively large. When conveying lighter items with certain corrosive properties, their mechanical properties are relatively excessive.

[0003] Conventional lightweight conveyor belts are generally made of thermoplastic polymer materials such as PVC and TPU. These materials have certain limitations in terms of wear resistance and corrosion resistance, and cannot meet the conveying requirements of customers in many conveying scenarios.

[0004] In the prior art, PEKK material has good structural regularity, high crystallinity and good thermal performance[1](Song Caisheng, Cai Mingzhong, Zhou Liyun, Acta Polymerica Sinica, 1995(1), 99-103). Except for a few strong acids such as concentrated sulfuric acid, it is almost insoluble in any organic solvent[2](Dai Runying, Song Caisheng, Zhong Ming, Xu Ling, Huang Hong, J Jiang Xi Normal University, 2007, 31: 518-522). Based on this, the present invention uses a new type of polymer material, polyether ketone ketone (PEKK), to make the surface material of the conveyor belt, which is in direct contact with the conveyed material. The high wear resistance and corrosion resistance of PEKK are used to meet the conveying requirements. However, since fluorine monomers are used in the production and processing of PEKK materials[3] (Mullins MJ,Woo EP J.Macromol Sci Rev Macromol Chem Phys:C, 1987,27:313-341), it is extremely difficult to combine PEKK with other conventional materials using chemical methods. At the same time, it is also difficult to bond PEKK with conventional materials using adhesives. Summary of the Invention

[0005] The present invention aims to provide a method for making a conveyor belt with high wear resistance, so as to solve the problem of easy wear of conveyor belts during use.

[0006] This invention discloses a method for manufacturing a high wear-resistant conveyor belt, comprising the following steps:

[0007] Step a: Fabric weaving and shaping;

[0008] Step b: Apply adhesive primer to both sides of the fabric;

[0009] Step c: Cast TPU film onto the fabric surface;

[0010] Step d: Heat-process the PEKK film surface into a limiting groove. After the TPU film on the fabric surface obtained in step c) is heat-melted, the PEKK film is stacked on the TPU film so that the limiting groove on the PEKK film surface is filled with TPU, so that the PEKK film is snapped onto the TPU film.

[0011] Preferably, the fabric in step a) is at least one layer, which can be a three-dimensional or single-layer fabric; wherein when the thickness of a single-layer fabric is insufficient, it can be laminated into a multi-layer fabric by means of a TPU film.

[0012] Preferably, step d) specifically includes the following steps: step d1) pressing concave patterns onto the PEKK film, the depth of which is 50% of the thickness of the PEKK film;

[0013] Step d2) A pair of rollers are used to press the upper and lower surfaces of the PEKK film respectively. The upper surface is pressed by a cooling roller, and the lower surface is heated and pressed by a heating roller with a limit groove pattern, so that the lower surface of the PEKK film forms a limit groove after being heated.

[0014] In step d3), when the processed PEKK film is pressed onto the TPU surface, the TPU is heated and penetrates into the various limiting slots of the PEKK film. After the TPU film cools and solidifies, it can be fixed by fitting into the corresponding limiting slots of the PEKK film.

[0015] Preferably, the limiting slot is a chamfered or L-shaped hook.

[0016] Preferably, the top coat adhesive is a two-component solvent-based TPU adhesive, comprising 15%-20% adhesive with a solid content, 4%-6% isocyanate curing agent, and the remainder being organic solvent.

[0017] Preferably, the reverse primer is a low-viscosity TPU two-component adhesive, comprising 15-18% solids content adhesive, 4%-6% isocyanate curing agent, and the remainder organic solvent.

[0018] The beneficial effects of this invention are:

[0019] The reinforcing layer of the conveyor belt of this invention can be made using a single layer of three-dimensional fabric or a multi-layer composite fabric structure. The weave of the bottom layer fabric can also be plain or twill depending on the noise requirements of the actual working conditions. The conveyor belt employs a multi-layer structure. The outermost layer of the surface portion in contact with the conveyed material is a PEKK film (0.05mm-0.1mm thick), the middle layer is polyurethane (hardness 65 Shore A), and the bottom layer is polyester fabric. To ensure the performance of the PEKK material, a special microstructure needs to be processed on the surface of the PEKK film, allowing the middle TPU layer to be embedded into the PEKK film surface, ensuring a stable bond between the two. This is achieved by physically bonding the PEKK film and polyurethane composite, thereby fixing the PEKK to the entire surface portion of the conveyor belt. This provides a lightweight conveyor belt that meets the requirements for conveying corrosive materials and demanding wear resistance. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the process of pressing concave patterns onto a PEKK film provided by the present invention;

[0021] Figure 2 This is a schematic diagram of the process of forming a chamfer after texturing the lower surface of the PEKK film provided by the present invention;

[0022] Figure 3 This is a schematic diagram of the process by which the PEKK film provided by the present invention is firmly bonded by beveling after TPU is penetrated into the texture;

[0023] Figure 4 This is a schematic diagram of Embodiment 1 of the conveyor belt provided by the present invention;

[0024] Figure 5 This is a schematic diagram of embodiment 2 of the conveyor belt provided by the present invention. Detailed Implementation

[0025] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0026] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0027] Example 1:

[0028] The conveyor belt provided in this embodiment has a one-cloth, two-rubber structure and is prepared through the following steps:

[0029] Step 1) Weave a layer of three-dimensional structure fabric:

[0030] The fabric is made of polyester with a warp density of 96±2 threads / inch (preferably 96 threads / inch) and a weft density of 56±2 threads / inch (preferably 56 threads / inch). The weave is a 2 / 1 twill with a herringbone structure. The warp yarns are made of 1000D low-shrinkage polyester activated yarn, interwoven in two layers at 100 rpm. The warp yarns are arranged with alternating S and Z twists. Between the two warp layers, 1000D low-shrinkage polyester activated yarns are arranged in a straight line at 100 rpm. The dry heat shrinkage of the low-shrinkage polyester activated yarn is ≤6.0%. Both the upper and lower weft layers are made of 0.3mm ultra-low shrinkage polyester monofilaments with a dry heat shrinkage of ≤1.0%, resulting in a three-dimensional structure fabric.

[0031] Step 2) Fabric setting:

[0032] The three-dimensional fabric obtained in step 1) is dried and shaped using an oven. The oven temperature is 200-210℃ (200℃ in this example), the tension is 450-500kg / m (470kg / m in this example), and the sizing speed is 9.5-10m / min (10m / min in this example) to ensure that the cross-sectional tension of the fabric is consistent and the temperature is uniform.

[0033] Step 3) Apply adhesive base coat to both sides:

[0034] The shaped fabric obtained in step 2) is then coated with adhesive primer on both sides. The adhesive primer on the front side ensures good peel strength with the cast surface layer to prevent delamination during use. The adhesive is a two-component TPU solvent-based adhesive with a solid content of 15%-20% (18% in this example), an isocyanate curing agent addition of 4%-6% (5% in this example), and a coating amount of 100-120 g / m² (110 m² in this example). 2 Infrared heating is used for drying at a temperature of 80-100℃ (90℃ in this example) and a drying speed of 6-7 m / min (6 m / min in this example) to ensure complete solvent evaporation and that the curing agent has not reacted. A reverse adhesive primer is used to seal the reverse fabric and bond it, improving its abrasion resistance. This primer uses a low-viscosity TPU two-component adhesive with a solid content of 15-18% (15% in this example) and a viscosity of 400-600 mPa·s (500 mPa·s in this example) to improve penetration. The isocyanate curing agent is added at 4%-6% (5% in this example), and the coating amount is 80-100 g / m² (90 g / m² in this example). 2 The product is dried using infrared heating at a temperature of 80-100℃ (90℃ in this embodiment) and a drying speed of 7-8m / min (7m / min in this embodiment).

[0035] Step 4) Casting TPU film and PEKK film:

[0036] The fabric with the adhesive base coat on both sides obtained in step 3) is extruded and cast onto the adhesive base coat surface on the front side to form a high-transparency TPU film. The casting die temperature is 190-210℃ (200℃ in this example), and the casting speed is 3.0-3.5m / min (3.2m / min in this example).

[0037] Concave patterns are embossed on the PEKK film, with a pattern depth of 50% of the PEKK film thickness. Figure 1 As shown; due to the excellent temperature resistance of PEKK, by precisely controlling the heating degree and time of the upper and lower surfaces, the textured surface of the lower surface can be softened while the upper surface remains unaffected. This is achieved by using a cooling roller to apply pressure to the upper surface of the PEKK film, ensuring the smooth surface is not deformed by temperature. Simultaneously, a heating roller heats and presses the lower surface of the PEKK film. After the lower surface texture softens, pressure is applied by a heated roller with a textured surface, deforming the lower half of the texture and forming a chamfer, as shown. Figure 2 As shown; when the processed PEKK film is pressed onto the TPU surface, the TPU is heated and penetrates into the texture of the PEKK film, that is, it penetrates into the chamfers on the lower surface of the PEKK film. After drying, the PEKK film and the TPU film are firmly bonded together by the chamfers. Figure 3 As shown.

[0038] The TPU film is laminated with the PEKK film through casting to form the final product, such as... Figure 4 As shown, the final product thickness is 1.5-1.55mm, of which the PEKK film layer thickness is 0.1mm, the TPU layer thickness is 0.4mm, and the three-dimensional structure fabric thickness is 1-1.05mm.

[0039] Example 2:

[0040] The conveyor belt provided in this embodiment is a multi-layer fabric composite structure (two fabrics and two adhesive layers). The difference between this embodiment and Embodiment 1 is that the fabric is polyester fabric, with 840D low-shrinkage polyester activated yarn used in the warp direction, twisted at 100 revolutions / meter, and the warp yarns arranged with alternating S and Z twists (dry heat shrinkage of low-shrinkage polyester activated yarn ≤6.0%); the weft direction uses 0.25mm ultra-low shrinkage polyester monofilament (dry heat shrinkage ≤1.0%); the warp density is 46±2 threads / inch (preferably 46 threads / inch), and the weft density is 40±2 threads / inch (preferably 40 threads / inch); the weave is a 1 / 1 plain weave structure. The first layer of the surface layer uses Shore A65±5 polyurethane material, the top layer uses 0.05mm PEKK film, and the bonding layer between the fabrics uses Shore A80±5 TPU material.

[0041] In this embodiment, the above-mentioned fabrics are coated with adhesive primer on both sides, and then cast and laminated to form a two-fabric-one-adhesive layer (thickness 1.3-1.35mm). The final product has a thickness of 1.75-1.8mm, wherein the PEKK film layer is 0.05mm thick, and the 65ATPU layer between the PEKK film layer and the fabric layer is 0.4mm thick. The final product is as follows. Figure 5 As shown.

[0042] Performance testing:

[0043] The PEKK-TPU bonding strength of the conveyor belt provided in Example 1 was tested, and the results are shown in Table 1. The PEKK film abrasion resistance of the conveyor belt provided in Example 1 was also tested, and the results are shown in Table 2.

[0044] Table 1. Bond strength between PEKK and TPU (ISO 253)

[0045]

[0046] Table 2 Abrasion resistance test of PEKK membrane (ASTM D1044)

[0047]

[0048] According to Tables 1 and 2, the bonding strength of the processed PEKK film is greater than that of the unprocessed film (i.e., the PEKK film is laminated with the TPU film by chamfering), the wear of the PEKK film is much less than that of 90A TPU, and the service life is greatly increased.

[0049] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for manufacturing a high wear-resistant conveyor belt, characterized in that, Includes the following steps: Step a: Fabric weaving and shaping; Step b: Apply adhesive primer to both sides of the fabric; Step c: Cast TPU film onto the fabric surface; Step d: Heat-process the PEKK film surface to generate limiting grooves on the surface. After heating the TPU film on the fabric surface obtained in step c), stack the PEKK film on the TPU film so that the limiting grooves on the PEKK film surface are filled with TPU. After cooling and shaping, the PEKK film is fixedly connected to the TPU film. Step d) specifically includes the following steps: Step d1) Press concave patterns onto the PEKK film; Step d2) Press the PEKK film on the upper and lower surfaces using a pair of rollers respectively, so that the lower surface of the PEKK film is heated to form a limiting groove. Step d3) When the processed PEKK film is pressed onto the TPU surface, the TPU is heated and penetrates into the various limiting slots of the PEKK film. After the TPU is cooled and formed, it fits into the corresponding limiting slots on the PEKK film. The thickness of the PEKK film is 0.05mm to 0.1mm.

2. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, In step a), the fabric is at least one layer, and can be a three-dimensional or single-layer fabric.

3. The method for manufacturing a high wear-resistant conveyor belt according to claim 2, characterized in that, In step a), when the thickness of a single-layer fabric is insufficient, it is laminated into a multi-layer fabric using a TPU film.

4. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, The texture depth is 50% of the PEKK film thickness.

5. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, The upper surface of the PEKK film is made smooth by applying pressure with a cooling roller, and the lower surface of the PEKK film is made by applying heat and pressure with a textured heating roller to form a limiting groove.

6. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, The limiting slot has a chamfer and an L-shaped hook.

7. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, The top adhesive base coat uses a two-component solvent-based TPU adhesive, including 15%-20% adhesive with a solid content, 4%-6% isocyanate curing agent, and the remainder organic solvent.

8. The method for manufacturing a high wear-resistant conveyor belt according to claim 1, characterized in that, The reverse adhesive base coat uses a low-viscosity TPU two-component adhesive, including 15-18% solid content adhesive, 4%-6% isocyanate curing agent, and the remainder organic solvent.

Citation Information

Patent Citations

  • Embossing device for flexible packaging composite film and embossing process

    CN107214942A

  • Laminate, method for manufacturing laminate, molded body, and method for manufacturing molded body

    CN111770796A

  • Micro-LED chip bearing substrate and manufacturing method thereof

    CN113506843A

  • Conveyor belt and manufacturing method of conveyor belt

    JP2017193441A